Proctologic Surgery Prioritization After the Lockdown: Development of a Scoring System - Pietroletti, Renato; Gallo, Gaetano; Muselli, Mario; Martinisi, Giovanbattista; Cofini, Vincenza (Frontiers in Surgery, 2022)
ABSTRACT INTRODUCTION. The COVID-19 pandemic has shown a very critical impact on surgical procedures all over the world. Italy faced the deepest impact from the beginning of March 2020. Elective operations, screening and follow-up visits had been suspended giving priority to urgent and oncologic surgery. PATIENTS. An observational study was carried out in the Surgical Coloproctology Unit of the Val Vibrata Hospital, on 152 patients awaiting a proctological surgical treatment at the date of national lockdown. METHODS. In order to monitor the health status of the patients and re-schedule post-lockdown surgical activities, patients were interviewed by telephone submitting a questionnaire based upon the judgement of an expert, senior clinician. Following the interview, we calculated a severity index for all proctologic diseases (hemorrhoidal disease, anal fissure, anal sepsis, slow transit or obstructed defecation, incontinence etc), classifying the patients according to the score. Mean age of patients was 53 (+/- 16) years and there were 84 males (55.3%) and 68 females (44.7%). Thirty-one percent of our patients suffered from anal fissure, 28% from hemorrhoidal disease, anal sepsis in 14%, other benign anorectal diseases in a lesser extent. RESULTS. One hundred-thirty-seven patients were available and divided into three classes: Priority Surgery (PS) with 49 patients (36.2%), Deferrable Surgery (DS) with 25 patients (18.1%) Long-term Surgery (L-TS) with 63 patients (45.6%) There was a significant correlation between the perceived health status reported during the interview and the Priority Class Index (Spearman rho=0.97, p<0.001). Differences related to age and sex were not significant (F test=0.43; p=0.653, chi2 test=0.693; p= 0.707). Forty-nine patients in class PS needed a prompt surgical treatment, while twenty-four patients allocated in class DS and sixty-five patients in class L-TS could wait for a new ride-plan for surgery. CONCLUSIONS. New tools like this simple score obtained at telephone interview, can be useful for prioritization patients on the waiting list for surgical coloproctology after lockdown without further clinical examination and hospital access.